Self Directed Learning Readiness between First Semester and Seventh Semester Medical Students in Faculty of Medicine Sebelas Maret University (UNS) - Putri, Deyona Annisa; ., Suyatmi; Ayusari, Amelya Augusthina (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2015)
Background: Problem Based Learning (PBL) has been applied by Faculty of Medicine Sebelas Maret Maret University Senate as a model of learning in Medical Education Program since 2007. One of the aim of PBL is increasing studentsâ Self Directed Learning (SDL) ability. SDL is a process in which individuals take the initiative, with or without the help of others, to diagnose their learning needs, formulate learning goals, identify resources for learning, select and implement learning strategies, and evaluate learning outcomes. SDL can be measured and represented by the level of Self Directed Learning Readiness (SDLR). One of the advantage of this research is evaluating PBL implementation in Faculty of Medicine Sebelas Maret University.Â So, the goal of this paper is to know the difference of self directed learning readiness between first semester andÂ seventh semester medical students in Faculty of Medicine Sebelas Maret University (UNS). Methods: This research was an analytical observational research using cross sectional approach and had been done in December 2014 in Faculty of Medicine Sebelas Maret University (UNS). The sample of this research were 386 of first and seventh semester students selected based on restriction criteria applying simple random sampling technique. Data was obtained using Self Directed Learning Readiness Scale-Nursing Education (SDLRS-NE) in Indonesian version and analyzed using Independent T-Test with SPSS 20.00 for Windows. Results: The mean of self directed learning readiness for the first UNS semester medical students was 149.09Â Â± 18.346 and for the seventh semester UNS medicalÂ students was 147.41 Â± 15.856. This research shows that there was not any significant difference of self directed learning readiness between two studied groups. The Independent t-Test shows p = 0.337. Conclusion: This study found that there was not any significant difference of self directed learning readiness between the first semester and the seventh semester UNS medical students. Keywords :Self Directed Learning Readiness, medical student, UNS Â